Nucleus Accumbens and Dopamine-Mediated Turning Behavior of the Rat: Role of Accumbal Non-dopaminergic Receptors - Hiroko Ikeda; Junzo Kamei; Noriaki Koshikawa; Alexander R. Cools (Elsevier, 2012)
Accumbal dopamine plays an important role in physiological responses and diseases such as schizophrenia, Parkinson's disease, and depression. Since the nucleus accumbens contains different neurotransmitters, it is important to know how they interact with dopaminergic function: this is because modifying accumbal dopamine has far-reaching consequences for the treatment of diseases in which accumbal dopamine is involved. This review provides a summary of these interactions, and our current knowledge about them are as follows: A) AMPA receptors are required for dopamine-dependent behavior and vice versa; NMDA receptors modulate the activity at the level of AMPA and/or dopamine D1 receptors. B) GABAA, but not GABAB, receptors inhibit dopamine-dependent behavior. C) Nicotinic receptors are required for dopamine-dependent behavior, whereas muscarinic receptors inhibit dopamine-dependent behavior. D) α-Adrenoceptors inhibit dopamine-dependent behavior in contrast to β-adrenoceptors, which potentiate this behavior. E) μ- and δ2-opioid receptors elicit behavior that requires an intact dopaminergic function and δ2-opioid receptors modulate dopamine-dependent behavior. F) Orexin 2 receptors play an important, modifying role in dopamine-dependent behavior. G) Somatostatin receptors potentiate dopamine-dependent behavior. It is suggested that modulation of the above-mentioned nondopaminergic receptors provide new tools to control physiological functions as well as diseases mediated by accumbal dopamine. Keywords:: dopamine, nucleus accumbens, turning behavior